Worker Directors: A German Product that Did Not Export? - Schnabel, Claus; Addison, John T. (Industrial relations, 2011)
Despite its seeming lack of attractiveness to other countries, the German system of quasi-parity codetermination at company level has held up fairly well. We recount the theoretical arguments for and against this form of codetermination, and survey the evolving empirical evidence on its economic impact. On both counts, employee representation on company boards might form part of the apparatus of good corporate governance, even if the extent of representation and the composition of the worker side are unsettled issues. Whatever the particular past merits of the case, however, the bottom line is that the recent availability of alternative forms of corporate governance will increasingly shape the German institution. © 2011 The Regents of the University of Californi
WiSo-Import:2015-03-26:1701